P19-91 The Safe and Sustainable by Design toolbox: guiding the user across the innovation stages through the SSbD Wizard - D. Sarigiannis; F. Nikiforou; A. Karakoltzidis; A. Agalliadou; J. Westra; V. Subramanian; T. Rydberg; M. Halling; I. Iavicoli; V. Leso; B. Nowack; J. Van Dijk; et al. (Toxicology Letters, 2024)

OS01-12 A computational toolbox supporting the development of Safe and Sustainable by Design chemicals and materials - D. Sarigiannis; F. Nikiforou; A. Karakoltzidis; A. Agalliadou; T. Rydberg; M. Halling; C.L. Battistelli; E. Benfenati; C. Bossa; E. Bouman; É. Bourgé; M. Brouwer-Milovanovic; et al. (Toxicology Letters, 2024)

A new species and a new record of Tylopilus (Boletaceae) of the balloui group in lowland and montane forests from Eastern Mexico - Montoya Leticia; Antero Ramos; Roy E. Halling; Victor M. Bandala (Mycological Progress, 2023)

Different environmental variables predict distribution and cover of the introduced red seaweed Eucheuma denticulatum in two geographical locations - M. Eggertsen; S. A. Tano; D. H. Chacin; J. S. Eklöf; J. Larsson; C. Berkström; A. S. Buriyo; C. Halling (Biological Invasions, 2021)
In this study we examined abiotic and biotic factors that could potentially influence the presence of a non-indigenous seaweed, Eucheuma denticulatum, in two locations, one outside (Kane’ohe Bay, Hawai’i, USA) and one within (Mafia Island, Tanzania) its natural geographical range. We hypothesized that the availability of hard substrate and the amount of wave exposure would explain distribution patterns, and that higher abundance of herbivorous fishes in Tanzania would exert stronger top–down control than in Hawai’i. To address these hypotheses, we surveyed E. denticulatum in sites subjected to different environmental conditions and used generalized linear mixed models (GLMM) to identify predictors of E. denticulatum presence. We also estimated grazing intensity on E. denticulatum by surveying the type and the amount of grazing scars. Finally, we used molecular tools to distinguish between indigenous and non-indigenous strains of E. denticulatum on Mafia Island. In Kane’ohe Bay, the likelihood of finding E. denticulatum increased with wave exposure, whereas on Mafia Island, the likelihood increased with cover of coral rubble, and decreased with distance from areas of introduction (AOI), but this decrease was less pronounced in the presence of coral rubble. Grazing intensity was higher in Kane’ohe Bay than on Mafia Island. However, we still suggest that efforts to reduce non-indigenous E. denticulatum should include protection of important herbivores in both sites because of the high levels of grazing close to AOI. Moreover , we recommend that areas with hard substrate and high structural complexity should be avoided when farming non-indigenous strains of E. denticulatum .

Contrasting distribution and foraging patterns of herbivorous and detritivorous fishes across multiple habitats in a tropical seascape - M. Eggertsen; D. H. Chacin; C. Åkerlund; C. Halling; C. Berkström (Marine Biology, 2019)

Biomass production and chemical composition of Moringa oleifera under different planting densities and levels of nitrogen fertilization - B. Mendieta-Araica; E. Spörndly; N. Reyes-Sánchez; F. Salmerón-Miranda; M. Halling (Agroforestry Systems, 2013)

Defensin Susceptibility and Colonization in the Mouse Model of AJ100, a Polymyxin B-Resistant, Brucella abortus RB51 Isolate - Shirley M. Halling; Allen E. Jensen; Steven C. Olsen (Current Microbiology, 2008)

Global diversity and distribution of macrofungi - Gregory M. Mueller; John P. Schmit; Patrick R. Leacock; Bart Buyck; Joaquín Cifuentes; Dennis E. Desjardin; Roy E. Halling; Kurt Hjortstam; Teresa Iturriaga; Karl-Henrik Larsson; D. Jean Lodge; Tom W. May; et al. (Biodiversity and Conservation, 2007)

Comparison of Spore Inoculated and Vegetative Propagated Cultivation Methods of Gracilaria chilensis in an Integrated Seaweed and Fish Cage Culture - C. Halling; G. Aroca; M. Cifuentes; A. H. Buschmann; M. Troell (Aquaculture International, 2005)

Tylopilus alkalixanthus, a new species of Boletaceae from Costa Rica and Japan - Anja Amtoft; Roy E. Halling; Gregory M. Mueller (Brittonia, 2002)

Ecological engineering in aquaculture: use of seaweeds for removing nutrients from intensive mariculture - M. Troell; P. Rönnbäck; C. Halling; N. Kautsky; A. Buschmann (Journal of Applied Phycology, 1999)